SnO2/MWCNTs Nanostructured Material for High-Performance Acetone and Ethanol Gas Sensors - Aleksanyan, Mikayel; Sayunts, Artak; Shahkhatuni, Gevorg; Simonyan, Zarine; Kananov, Davit; Khachaturyan, Emma; Papovyan, Rima; Michalcová, Alena; Kopecký, Dušan (ACS omega, 2025)
This work presents a novel nanostructured material SnO2/multiwalled carbon nanotubes (MWCNTs) as a sensing film for the detection of acetone and ethanol vapors. The fabrication of SnO2/MWCNT chemoresistive sensors demonstrates a cost-effective hydrothermal method using a centrifugation technique. The material investigation of the synthesized SnO2/MWCNTs nanocomposite represents various techniques, such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy-dispersive X-ray (EDX) elementary analysis, EDX mapping, and X-ray diffraction (XRD) analysis. The SnO2/MWCNTs sensor exhibits rapid response/recovery behavior toward acetone (53/5 s) and ethanol (86/3 s) while showing satisfactory values of responsiveness (S act = 90.5 and S etn = 21, n = 100 ppm). The low detection limit of these vapors is assigned a concentration of 1 ppm, where discernible responses are elicited. Thus, the SnO2/MWCNTs sensor production efforts have yielded a high-end volatile organic compound (VOC) detector, highly suitable for human technological and engineering activity.